Metabolic engineering of Escherichia coli for efficient production of l-alanyl-l-glutamine - Zhu, Jiangming; Yang, Wei; Wang, Bohua; Liu, Qun; Zhong, Xiaotong; Gao, Quanxiu; Liu, Jiezheng; Huang, Jianzhong; Lin, Baixue; Tao, Yong (Microbial cell factories, 2020)
L-Alanyl-L-glutamine (AQ) is a functional dipeptide with high water solubility, good thermal stability and high bioavailability. It is widely used in clinical treatment, post-operative rehabilitation, sports health care and other fields. AQ is mainly produced via chemical synthesis which is complicated, time-consuming, labor-intensive, and have a low yield accompanied with the generation of by-products. It is therefore highly desirable to develop an efficient biotechnological process for the industrial production of AQ. A metabolically engineered E. coli strain for AQ production was developed by over-expressing L-amino acid α-ligase (BacD) from Bacillus subtilis, and inactivating the peptidases PepA, PepB, PepD, and PepN, as well as the dipeptide transport system Dpp. In order to use the more readily available substrate glutamic acid, a module for glutamine synthesis from glutamic acid was constructed by introducing glutamine synthetase (GlnA). Additionally, we knocked out glsA-glsB to block the first step in glutamine metabolism, and glnE-glnB involved in the ATP-dependent addition of AMP/UMP to a subunit of glutamine synthetase, which resulted in increased glutamine supply. Then the glutamine synthesis module was combined with the AQ synthesis module to develop the engineered strain that uses glutamic acid and alanine for AQ production. The expression of BacD and GlnA was further balanced to improve AQ production. Using the final engineered strain p15/AQ10 as a whole-cell biocatalyst, 71.7 mM AQ was produced with a productivity of 3.98 mM/h and conversion rate of 71.7%. A metabolically engineered strain for AQ production was successfully developed via inactivation of peptidases, screening of BacD, introduction of glutamine synthesis module, and balancing the glutamine and AQ synthesis modules to improve the yield of AQ. This work provides a microbial cell factory for efficient production of AQ with industrial potential.